DNA microarrays to identify etiological agents, as sensors of environmental wellbeing - Arena-Ortiz, María Leticia; Sánchez-Rodríguez, Ernesto Cuauhtemoc; Apodaca-Hernández, Javier Eduardo; Ortiz-Alcántara, Joanna María; Ríos-Contreras, Karen; Chiappa-Carrara, Xavier (Frontiers in Bioengineering and Biotechnology, 2023)
The epidemiologic transition in Mexico has generated a change of paradigm in public health. Morbidity is characterized by infectious diseases and the mortality is due to chronic degenerative diseases. The three most important infectious diseases in the country are: respiratory infections, diarrhea, and urinary tract infections. The objective of this work was to build a tool to monitor the presence of health risks in the environment in a timely manner and to demonstrate its application in different sicknesses, especially those that are water related. In this study, we analyzed water samples from five cenotes with high tourist flow in the State of Yucatan. We developed a DNA microarray for the adequate and prompt detection of viruses, bacteria, fungi, and parasites. This microarray could be used in samples of different origin including air, water (fresh, brackish and saltwater), food, inert surfaces or wounds. Clinically, it would allow prompt and precise detection of etiological agents of infectious diseases to prevent outbreaks. It would also be useful for the identification of those agents that cannot be detected in our laboratories with the traditional methods. Finally, it could be an important tool to monitor the evolution of infectious diseases and to prevent antibiotic resistance in hospitals. It includes 38,000 probes that detect 252 etiological agents of diseases in humans and antimicrobial resistance genes. Results from DNA samples can be obtained in 24 hours, which would be difficult or impossible using other technologies. The water samples analyzed from cenotes detected 228 different bacteria, viruses, fungi, and protozoa. They are amongst the most important etiological agents for infectious diseases in Mexico. This microarray is a useful tool for early detection of infectious agents in individuals, hospitals and natural environments, to reduce health risks.